SLAP Repairs With Combined Procedures Have Lower Failure Rate Than Isolated Repairs in a Military Population: Surgical Outcomes With Minimum 2-Year Follow-up. Issue 8 (14th August 2015) - Waterman, Brian R.; Arroyo, William; Heida, Kenneth; Burks, Robert; Pallis, Mark
Background: Injuries to the superior glenoid labrum represent a significant cause of shoulder pain among active patients. The physical requirements of military service may contribute to an increased risk of injury. Limited data are available regarding the success of superior labral anterior posterior (SLAP) repairs in an active military population. Purpose: To quantify the rate of clinical failure and surgical revision after isolated and combined SLAP repair. Study Design: Cohort study; Level of evidence, 3. Methods: All consecutive active-duty servicemembers undergoing arthroscopic repair of type II SLAP lesions at a single institution between 2006 and 2012 were identified. Patients with less than 2-year clinical follow-up and nonmilitary status were excluded. Demographic variables, surgical variables, and occupational outcomes were extracted from electronic medical records and confirmed with the US Army Physical Disability Agency database. Failure was defined as subsequent revision surgery or medical discharge with persistent shoulder complaints. Results: A total of 192 patients with SLAP repair were identified with a mean follow-up of 50.0 months (SD, 17.0 months). Isolated SLAP repair occurred in 31.3% (n = 60) versus 68.8% (n = 132) with concomitant procedures. At final follow-up, 37.0% (n = 71) of patients reported some subjective activity-related shoulder pain. Postoperative return to duty occurred in 79.6% (n = 153), and only 20.3% (n = 39) were discharged with continuing shoulder disability. The combined rotator cuff repair (96%; P = .023) and anteroinferior labral repair group (88%; P = .056) had a higher rate of functional return than isolated SLAP repair (70%). Thirty-one (16.1%) patients were classified as surgical failure and required revision. Of these, the majority of patients undergoing biceps tenodesis (76%) returned to active duty, as compared with revision SLAP repair (17%). Lower demand occupation and the presence of combined shoulder injuries ( P = .011 and .016, respectively) were significantly associated with a lower risk of medical discharge and revision surgery, respectively. Conclusion: Favorable outcomes can be anticipated in the majority of military servicemembers after arthroscopic SLAP repair, particularly with combined shoulder injuries. Revision surgery occurred in 16% of patients after primary SLAP repair. Clinical Relevance: Isolated repair of unstable SLAP lesions and/or increased upper extremity demands are associated with higher failure rates in this population.